2004
DOI: 10.1603/0022-0493-97.6.1797
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Native and Recombinant Cry1B Protein Against Experimentally Induced and Naturally Acquired Ovine Myiasis (Fly Strike) in Sheep

Abstract: Several hundred strains of Bacillus thuringiensis (Bt), isolated in New Zealand from samples of soil and sheep fleece, were tested for toxicity to larvae of the blowfly Lucilia cuprina Wiedemann. Characterization of the Bt strains revealed that three of the more active strains produced Cry1Ba (an insecticidal protein present in Bt mother cell crystal inclusion) that was toxic to blowflies. These strains were evaluated for the ability to prevent experimentally induced fly strike in a bioassay by using first ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…35 In certain parts of the world, routine dipping or spraying with larvicidal compounds is used for prevention and control. Fly sprays should be used on and around any wounds.…”
Section: Preventionmentioning
confidence: 99%
“…35 In certain parts of the world, routine dipping or spraying with larvicidal compounds is used for prevention and control. Fly sprays should be used on and around any wounds.…”
Section: Preventionmentioning
confidence: 99%
“…The use of B. thuringiensis to control flystrike has been investigated by using B. thuringiensis strains applied to sheep fleece [5,6] resulting in protection from flystrike for 6-11 weeks. B. thuringiensis has also been shown to be common in sheep fleece [5][6][7]. These studies did not distinguish between insecticidal effect due to d-endotoxins and b-exotoxins which are general RNA synthesis inhibitors produced by some B. thuringiensis strains.…”
Section: Introductionmentioning
confidence: 88%
“…thuringiensis-based products are widely used as efficient bio-pesticides against a number of lepidopteran and coleopteran pests, and more than 29 million acres of B. thuringiensis genetically modified crop fields are grown globally. Recently, a number of B. thuringiensis strains that have specific activity against livestock insect pests including larvae of the sheep blowfly [7][8][9] have been identified. The use of B. thuringiensis to control flystrike has been investigated by using B. thuringiensis strains applied to sheep fleece [5,6] resulting in protection from flystrike for 6-11 weeks.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of field-isolated strains of Bt have been shown to produce toxins that are active against blowfly larvae in vitro and in vivo. [52][53][54][55] Heath et al 53 showed that Bt extracts applied to patches on sheep were able to protect sheep from experimentally induced flystrike (implants) for up to 6 weeks. A time-course study showed that protection from flystrike was not diminished by exposure of sheep to precipitation or sunlight, but, rather, the loss of protection over time was considered to be most likely due to movement of the toxin away from the skin as the wool grew.…”
Section: Biological Controlmentioning
confidence: 99%